Eliciting Idiom Retention through Alliteration in a Classroom Activity - Dwi Wahyuningtyas (Masters in English Education, The Directory of Postgraduate Program,Universitas Muhammadiyah Malang, 2021)
Alliteration comes up as one of the efforts that follow the notion of linguistic motivation in creating language retention and memorization to learners. Idiom is one of the language phenomena where alliteration takes place as part of its non-arbitrariness principle. The claim underlying the effectiveness of alliteration in aiding language retention in idiom is tried to be applied in some classroom activities which may consist of pre, whilst, and post-teaching. All the activities in the teaching session are arranged to be integrated with idiom learning using alliteration. Learners' ability to recall idioms containing aliteration will also be tested in the provided exercises. The success of the expected retention on learners will be measured from the result gained from the activity divided simply into three phases, pre-teaching, whilst-teaching, and post-teaching where it will be conducted for approximately 90 minutes. As some deviations possibly made can influence the result, the teacher should figure out some considerations affecting the effectiveness of the lesson given. Reflection phase should be conducted maximally, so that learners’ response is really fruitful that it can be known whether they are engaged with the activity and gain the material well. In the first activity, they work semi-independently, so that the assessment is expected to be more objective, covering the combination of group and individual work.